Effectiveness of Marketing Practices as Determinants of Purchase Intention for POP Mart Products: Insights from Filipino Consumers - Neil Owen Andre Recato; Russel C. Remulta; Norman Lesther S. Respicio; Shemaiah Janelle C. Santomin (The Indonesian Institute of Science and Technology Research, 2026)
This study examined the effectiveness of marketing practices, particularly the 4Ps of marketing mix, and consumer purchase intention for POP Mart products among Gen-Z Filipino consumers to determine the relationship between the effectiveness of the 4Ps marketing mix practices and the purchase intention of Gen Z Filipino consumers for POP Mart products. Using a quantitative correlational design, 385 respondents from Metro Manila were familiar with or had purchased POP MART products. Descriptive statistics and Pearson correlation analysis were employed to determine the correlation of the two variables. Results revealed that all four of the marketing mix components were positively rated, indicating that respondents generally agreed with POP Mart’s marketing strategies. Among the 4Ps, Product received the highest level of agreement, emphasizing strong influence on quality, design, and novelty on consumer decisions. The Pearson correlation coefficient (r = 0.668, p < 0.05) showed a moderately strong, positive, and statistically significant relationship between marketing practices and purchase intention, indicating that higher perceived marketing effectiveness increases consumers’ willingness to purchase. This concludes that the effective implementation of the 4Ps significantly influences the purchasing behavior of Gen Z Filipino consumers regarding collectible products. It gives viable information to both POP Mart Philippines and marketing professionals on how to develop specific, experience-based, and culturally responsive approaches to consumer appreciation and brand affinity. Furthermore, the study adds to the scarcity of local literature on marketing effectiveness in the Philippine context and highlights the potential of active retail industries to facilitate the development of sustainable economic growth.